A influência no processo de treino da tríade: treino, jogo e adversário - Gabriel Gomes Silva (2016)
The training process is assumed to be the principal way to improve both individual and collective performance in soccer. From this premiss, we established the objectives of this professional internship, realized during a Master Degree in High Performance Sports at the Faculty of Sports of the University of Porto. This report aims to fundamentally present and reflect on the student's experiences. To do so, the decisions that were made are discussed in respect with different thematics, such as training planning, its operationalization, and its evaluation. We emphasize on the importance of the planning and periodization process of the training, and of its operationalization based on the evaluation of the team and its training program, as well as the analysis of the opponent.